THE PRACTICAL OF AN EXPLORATORY FACTOR ANALYSIS: THE EVIDENCE FROM THE INTEGRATION OF TECHNOLOGICAL SUPPORT ON KNOWLEDGE MANAGEMENT - Farahiyah Akmal Mat Nawi; Prof. Dr Abdul Malek A.Tambi (International Journal of Accounting, Finance and Business, 2020)
This paper aimed to provide explicit information for the researchers with basic knowledge of exploratory factor analysis (EFA) on how the analysis procedure can be carried out appropriately. Furthermore, the reason of applying this analysis because it hypothesizes underlining concepts generated in the initial analysis or invalidates the research findings. Generally, the application of EFA is applicable to make appropriate decisions as to whether to retain or drop an item from the analysis to attain an interpretable factor solution. As for the practical of analysis the study was conducted to 104 lecturers from UiTM Kelantan and questionnaire consists of 20 questions with 7 scales was used to gather the data to identify the integration of technology support in knowledge management activity. Nowadays organizations are constantly striving to develop and enhance knowledge of employees who involve in strategic business processes by which they aim for an organizational knowledge creation to achieve a competitive advantage. The knowledge management has become as a vital part of the institution strategy to manage the tangible and intangible information assets of the institutions. With the integration of technology support components, it would be able to increase the efficiency of the knowledge management process. To identify the effectiveness of the integration the independent (technology support) and dependent (knowledge management) variables was tested. For the preliminary analysis the reliability analysis resulted strong associations (greater than 0.6) of the variables and the EFA result explain all the indicators were successfully achieved the minimum requirement (factor loadings are greater than 0.6) and all items are retaining for further analysis. The finding obtained has proven that the research’s instrument has high reliability and validity.